2015
DOI: 10.1038/bjc.2015.256
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and anti-tumour activity of olaparib monotherapy after combination with carboplatin and paclitaxel in patients with advanced breast, ovarian or fallopian tube cancer

Abstract: Background:Olaparib (AZD2281), a PARP-1/2 inhibitor, has been extensively investigated in clinical trials. However, limited clinical data are available about its long-term safety and anti-tumour activity.Methods:Patients had first participated in a phase I study of olaparib combined with carboplatin and/or paclitaxel. They continued with olaparib monotherapy in their best interest if they failed to tolerate the combination due to the treatment-related adverse events (TRAEs). Safety data were collected by physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Hypokalemia was the only TEAE reported in ≥ 10% of patients. During the once-daily niraparib dosing phase (i.e., after the substudy), the grade ≥ 3 TEAE profile (Table 5) was consistent with the safety profile seen in other niraparib studies [15] and other PARP inhibitors [19][20][21]. There were no reports of clinically significant abnormal ECG changes, including QTc interval prolongation, attributed to niraparib.…”
Section: Safetysupporting
confidence: 76%
“…Hypokalemia was the only TEAE reported in ≥ 10% of patients. During the once-daily niraparib dosing phase (i.e., after the substudy), the grade ≥ 3 TEAE profile (Table 5) was consistent with the safety profile seen in other niraparib studies [15] and other PARP inhibitors [19][20][21]. There were no reports of clinically significant abnormal ECG changes, including QTc interval prolongation, attributed to niraparib.…”
Section: Safetysupporting
confidence: 76%
“…Similarly, dose-escalation studies of Olaparib in combination gemcitabine (15), doxorubicin (16), and paclitaxel (17) found that the monotherapy daily dose (400mg b.i.d) could not be reached with an acceptable tolerability profile. In contrast, daily Olaparib maintenance therapy after combination therapy was well tolerated (18). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PARP-1 and PARP-2 also participate in other biological functions such as angiogenesis and transcription [12,13], apoptosis of oxidative-stress related pathologies [14][15][16], and regulation of the immune response [11,12]. On the other hand, an increased activity or overexpression of PARP-1 and -2 may also induce cellular damage by depleting the ATP stores of cells in several conditions [17][18][19][20] or by altering the mechanisms of DNA repair, leading to tumorogenesis of several cancer types [12,[21][22][23][24]. Therefore, the role of PARP-1 and PARP-2 in cells is two-fold: while they play a critical role in DNA repair, they may also favor carcinogenesis and tumor progression [12,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an increased activity or overexpression of PARP-1 and -2 may also induce cellular damage by depleting the ATP stores of cells in several conditions [17][18][19][20] or by altering the mechanisms of DNA repair, leading to tumorogenesis of several cancer types [12,[21][22][23][24]. Therefore, the role of PARP-1 and PARP-2 in cells is two-fold: while they play a critical role in DNA repair, they may also favor carcinogenesis and tumor progression [12,[21][22][23][24][25]. In line with the latter, PARP-1 overexpression was also shown to correlate with poor survival of patients with breast cancer [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation